Diagnostic accuracy of frozen section in borderline ovarian tumors - Palumbo, Giuseppina; Giordano, Giovanna; Dall'Asta, Andrea; Monica, Michela; Mautone, Daniele; Di Serio, Maurizio; Berretta, Roberto (European Journal of Oncology and Environmental Health, 2015)
Background: Borderline ovarian tumors (BOTs) are an intermediate form between benign and malignant neoplasms. BOTs occur more frequently in stage I and in young women who desire progeny. Several studies have shown that conservative treatment (unilateral oophorectomy) or ultra-conservative (cystectomy) are an oncologically safe choice in terms of survival. Frozen section histology is considered reliable to exclude the presence of malignant lesions in suspicious masses. The aim of this study was to evaluate the diagnostic accuracy of intraoperative histological examination in borderline tumors of the ovary. Patients and methods: We retrospectively collected 627 patients with a ovarian eteroplasia treated at the University Hospital of Parma between January 1, 1994 and December 31, 2012. 124 of these had a final diagnosis of BOT (19.8%). Among those, 39 adnexal masses were analyzed in the 37 patients included in the study who underwent intraoperative frozen section of the surgical specimen. Results: Group 0 included patients whose definitive histological examination disagreed with the extemporaneous examination, while group 1 included those patients in whom intraoperative and final diagnosis agreed. Groups 0 and 1 did not statistically differ in regard to clinical and laboratory features. Histotype and tumor size affected frozen section diagnostic accuracy. Frozen section accuracy was higher in serous BOTs; extemporaneous examination performed best upon maximum diameters of less than 8.6 cm. Conclusion: Frozen section is an accurate and useful method for surgical management of suspicious adnexal masses.